Public Health Policy in The Bahamas: An Overview - Sands, Duane; Moxey, Cherita (International Journal of Bahamian Studies, 2021)
This edited transcript was a public lecture delivered by Dr. Duane Sands, MP and Minister of Health at the University of The Bahamas on May 2, 2019 as part of the “Meet the Policy Makers Series” sponsored by the Government and Public Policy Institute of the University of The Bahamas.